Archaeological and Paleontological Research in Lagoa Santa : The Quest for the First Americans - Da-Gloria, Pedro; Neves, Walter A.; Hubbe, Mark (Springer International Publishing : Imprint: Springer, 2017)
This groundbreaking volume presents, for the first time in English, a broad historical review of the researches carried out over 170 years in the region of Lagoa Santa, Brazil, one of the most important archaeological regions in the Americas. From the pioneering work of the Danish naturalist Peter Lund in the 19th century to the recent research on the dispersion of early humans across South America, led by Walter A. Neves and colleagues, Lagoa Santa has offered remarkable findings, the largest collections of early human skeletons in the Americas, and has contributed to the overall discussions about the settlement of the Americas. This edited volume aims to fill the lack of publications in English about Lagoa Santa and to gather representatives of all the main Brazilian institutions directly involved in the archaeological and paleontological investigations in the region, in order to provide the international scientific community a comprehensive and complete account of the researches that contributed to rewrite the history of the peopling of the Americas. The book is organized in two parts. The first consists of chapters describing each of the interventions in the region, beginning with the pioneering work of Peter Lund and culminating with the latest intervention led by Walter A. Neves and his team. The second part of the book consists of reviews of current relevant research foci in the region, such as migrations, health, mortuary rituals, paleontology, rock art, technology, and geoarchaeology.